HUKUM BERMAIN GAME ONLINE PLAYER UNKNOWN’S BATTLEGROUNDS (PUBG) MENURUT FATWA MPU ACEH NOMOR 3 TAHUN 2019 - Khairuddin (DIKTUM: Jurnal Syariah dan Hukum, 2020)
Abstract: This study is entitled The Law of Playing Unknown's Battle Grounds (PUBG) Game According to MPU Fatwa Aceh No. 3 of 2019 (Case Study in Gunung Meriah District, Aceh Singkil Regency). This study describes how the factors and the impact of PUBG online game play and what is the view of the MPU Aceh on the law of playing PUBG games ?. To obtain answers to these problems, the authors used three data collection methods; Observation, interview and documentation. The sample in this study was PUBG online gamers in Gunung Meriah Sub-district, Aceh Singkil District. The results of this study indicate that 25% of the community of Gunung Meriah Liking and categories are addicted to the PUBG game. The main factor of playing PUBG games. Playing hobbies online, including PUBG, can reduce boredom and stress. Games that continue to be carried out have unfavorable effects such as tend to be more lazy, addictions that are not fair, less response to the surrounding environment. In Islam, banning PUBG games is in line with the MPU Aceh fatwa no. 3 of 2019, the reason for it is forbidden to use this one game, because it contains elements of violence and brutality and the impact of changing the behavior of users becomes negative; because it has the potential to cause aggressive behavior and addiction at a high level; and contains elements of insult to Islamic symbols. because it contains elements of violence and brutality as well as negative changes in the behavior of users; because it has the potential to cause aggressive behavior and addiction at a high level; and contains elements of insult to Islamic symbols. because it contains elements of violence and brutality as well as negative changes in the behavior of users; because it has the potential to cause aggressive behavior and addiction at a high level; and contains elements of insult to Islamic symbols.